Comparison of disease activity measures for anti-neutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis. Issue 1 (29th July 2008) - Merkel, P A; Cuthbertson, D D; Hellmich, B; Hoffman, G S; Jayne, D R W; Kallenberg, C G M; Krischer, J P; Luqmani, R; Mahr, A D; Matteson, E L; Specks, U; Stone, J H; et al.
Abstract : Aim: Currently, several different instruments are used to measure disease activity and extent in clinical trials of anti-neutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis, leading to division among investigative groups and difficulty comparing study results. An exercise comparing six different vasculitis instruments was performed. Methods: A total of 10 experienced vasculitis investigators from 5 countries scored 20 cases in the literature of Wegener granulomatosis or microscopic polyangiitis using 6 disease assessment tools: the Birmingham Vasculitis Activity Score (BVAS), The BVAS for Wegener granulomatosis (BVAS/WG), BVAS 2003, a Physician Global Assessment (PGA), the Disease Extent Index (DEI) and the Five Factor Score (FFS). Five cases were rescored by all raters. Results: Reliability of the measures was extremely high (intraclass correlations for the six measures all = 0.98). Within each instrument, there were no significant differences or outliers among the scores from the 10 investigators. Test/retest reliability was high for each measure: range = 0.77 to 0.95. The scores of the five acute activity measures correlated extremely well with one another. Conclusions: Currently available tools for measuring disease extent and activity in ANCA-associated vasculitis are highly correlated and reliable. These results provide investigators with confidence to compare different clinical trial data and helps form common ground as international research groups develop new, improved and universally accepted vasculitis disease assessment instruments.